2007
DOI: 10.1577/t06-037.1
|View full text |Cite
|
Sign up to set email alerts
|

Fine‐Scale Population Structure of Rainbow Trout in the Spokane River Drainage in Relation to Hatchery Stocking and Barriers

Abstract: We used 13 microsatellite loci to examine population structure in rainbow trout Oncorhynchus mykiss collected from 20 tributaries and 3 main stems in the greater Spokane River drainage. Populations displayed some excess homozygosity and linkage disequilibrium, which was more pronounced in upper tributary collections and probably the result of small effective population sizes or structuring within tributaries. In general, population structure followed geographic structure; collections from creeks within sub‐dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 48 publications
2
32
0
Order By: Relevance
“…In the Spokane River drainage of Washington, Small et al (2007) describe introgression of local wild populations in some areas exposed to hatchery stocking, whereas other stocked areas show minimal genetic relationship to hatchery collections. Taylor et al (2007) found low levels of introgression among divergent hatchery and wild O. mykiss in the Athabasca River that was restricted to a select few localities within the basin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Spokane River drainage of Washington, Small et al (2007) describe introgression of local wild populations in some areas exposed to hatchery stocking, whereas other stocked areas show minimal genetic relationship to hatchery collections. Taylor et al (2007) found low levels of introgression among divergent hatchery and wild O. mykiss in the Athabasca River that was restricted to a select few localities within the basin.…”
Section: Discussionmentioning
confidence: 99%
“…Despite apparent restricted geneflow between OSH and CPR, there are no geographic or physical barriers that preclude the opportunity to interbreed, and it is probable that interbreeding does occur to some extent. The persistence of a genetically distinct CPR population is likely due to differences in life histories and/or utilization of spawning habitat or assortative mating behavior between populations (Narum et al 2004;Small et al 2007). The CPR redband trout population maintains a relatively strict adfluvial life history utilizing reservoir tributaries beginning in January and extending through May.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining inland areas that have coastal haplotypes are all in eastern Washington (localities 18, 24–26). Localities 18 and 25 represent areas that have documented stocking activities for the past 70 years (Small et al 2007) and coastal haplotypes in the area may represent introgression of coastal-derived hatchery stock into the native inland populations. Locality 24, the Wells Steelhead Hatchery, also contained coastal haplotypes and may have used milt from coastal steelhead to propagate inland populations (Thorgaard 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The coastal and inland lineages are recognized by differences in coloration and numbers of pyloric caecae, scales along the lateral line, vertebrae and gill rakers (Behnke 1992). Differences in microsatellite and allozyme frequencies have often been used to study introgression and hybridization between these subspecies (Utter 2001, Knudsen et al 2002, Small et al 2007). …”
Section: Introductionmentioning
confidence: 99%